ENT 530 Social Media Portfolio: Tornado Cheese Cake / Lokman Hakim Mazlan - Mazlan, Lokman Hakim (2021)
Tornado Cheese Cake is an online business about dessert that focus more to chocolate cheese cake. The Tornado Cheese Cakes has only one recipe and offering which is the chocolate cheese cake because the business is focusing on directly to people who love chocolate cheese cakes so that they know where to find and get it easier. Focusing on one particular product is easier and makes the product produced to be better in quality and quantity and so that the consumer get to enjoy it with cheerful and ease. Chocolate has been studied as a stress reliever and gives joy to it consumer and cheese can benefits the heart due to it rich in calcium, protein and vitamins also because of it delicious taste. This online business offers and affordable price for the only two size product which is RM15 for the small size and RM20 for the bigger size so that people from various income can afford to buy and consume the tornado cheese cakes. Tornado Cheese Cake main marketing strategy is providing and producing the best taste and quality of the product and services and not only that also for the price to be affordable so that customer could enjoy the product more. By having a good quality of a product, consumer will surely seek for the product and spread the words of the particular product is good in quality and taste will increase the sales of the business and by having a great customer service, it can benefit the business by having a good relationship and bond that can give the business customer loyalty which is a great benefit and at the same time it will generate more profits to the business. The Tornado Cheese Cakes online business is manage individually by me, Lokman Hakim bin Mazlan. I created this Facebook Page is to get involve in Food and beverage industry business and to generate profit and due to covid19 pandemic it is a great way to generate income due to people aren’t able to go freely finding desserts. To get my product known, Promoting and making an offer is a must so that people know about my Tornado Cheese Cake product and getting the likes and follower so that people are convinced to buy and consume my product with more trust and at the same time to gain profit. Even though it is quite challenging for me to consistently promote on the Facebook Page but I do my best to fulfill it.